2016
DOI: 10.2147/phmt.s77568
|View full text |Cite
|
Sign up to set email alerts
|

Management options for pediatric patients who stutter: current challenges and future directions

Abstract: Stuttering is a speech disorder, with onset often occurring in the preschool years. The prevalence of stuttering in young children is much higher than that in the general population, suggesting a high rate of recovery. However, we are unable to predict which children will recover without treatment, and it is widely acknowledged that stuttering therapy during childhood provides the best safeguard against chronic stuttering. This review reports on current evidence-based stuttering treatment options for preschool… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 76 publications
1
2
0
1
Order By: Relevance
“…Findings of current study are fairly reliable with previous studies in literature which report that the digital manipulation of thyroid cartilage and fluency shaping therapy are effective techniques to reduce the severity of stuttering 18,19 . Therefore, suggested that DMTC and FST would reduce the severity of stuttering, however the combination of both would remarkably reduce the severity of stuttering than single alone.…”
Section: Discussionsupporting
confidence: 88%
“…Findings of current study are fairly reliable with previous studies in literature which report that the digital manipulation of thyroid cartilage and fluency shaping therapy are effective techniques to reduce the severity of stuttering 18,19 . Therefore, suggested that DMTC and FST would reduce the severity of stuttering, however the combination of both would remarkably reduce the severity of stuttering than single alone.…”
Section: Discussionsupporting
confidence: 88%
“…Estão disponíveis modelos de intervenção indireta ou direta com terapia da fala, 30,32 entre os quais se destaca o Lidcom-Program of early stuttering intervention. 33 Apesar de após os sete anos, ser pouco provável que a disfluência possa ser ultrapassada, qualquer pessoa, independentemente da sua idade, beneficiaria de intervenção terapêutica com potenciais ganhos na redução da severidade e do impacto da gaguez na sua vida. 10 O uso de farmacoterapia não está recomendado nas perturbações da fluência, mesmo em adolescentes e adultos.…”
Section: Intervençãounclassified
“…Addressing such feelings is important because they can disrupt the healing process and prevent parental change (25,26). The most effective options for early intervention are stuttering through parental cooperation, in which the clinician acts as a facilitator., However Practicing regular treatment at home can also be challenging, especially if both parents are working, and if parents or siblings are separated (21). Another study examines the impact of telemedicine on parent participation in pediatric intensive care, the results show that all parents reported that telemedicine approaches had a positive effect on their confidence in child care and improved communication with the care team (26).…”
Section: Ensuring Follow-up Treatment By the Family And Improving Parent-child Relationsmentioning
confidence: 99%